A systematic review of grounded theory studies in physiotherapy. (2nd December 2019) - Ali, Nancy; May, Stephen; Grafton, Kate
ABSTRACT: Aim: This systematic review aimed at appraising the methodological rigor of grounded theory research published in the field of physiotherapy to assess how the methodology is understood and applied. A secondary aim was to provide research implications drawn from the findings to guide future grounded theory methodology (GTM) research. Methods: A systematic search was conducted in MEDLINE, CINHAL, SPORT Discus, Science Direct, PubMed, Scopus, and Web of Science to identify studies in the field of physiotherapy that reported using GTM and/or methods in the study title and/or abstract. The descriptive characteristics and methodological quality of eligible studies were examined using grounded theory methodology assessment guidelines. Findings: The review included 68 studies conducted between 1998 and 2017. The findings showed that GTM is becoming increasingly used by physiotherapy researchers. Thirty-six studies (53%) demonstrated a good understanding and appropriate application of GTM. Thirty-two studies (47%) presented descriptive findings and were considered to be of poor methodological quality. Conclusions: There are several key tenets of GTM that are integral to the iterative process of qualitative theorizing and need to be applied throughout all research practices including sampling, data collection, and analysis.